Prediksi Kebangkrutan dengan Altman Z-Score Modifikasi (Studi Kasus Pada PT Smartfren Telecom Tbk Periode 2011-2020) - Annisa Nur Safitri; Mochamad Edman Syarief; Tjetjep Djuwarsa (Indonesian Journal of Economics and Management, 2021)
The purpose of this research was to determine how the prediction of bankruptcy at PT Smartfren Telecom Tbk for the period 2011-2020. The method used in this research is quantitative descriptive research and the data used are secondary data obtained from financial report published by PT Smartfren Telecom Tbk for the period 2011-2020. The analysis technique used in this research is the Altman Z-Score Modification method which uses four ratio variables is Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), EBIT to Total Assets (X3), and Book Value Equity to Book Value of Debt (X4). The results showed that the company was in a bad condition because in 2011 to 2020 the company was included in the unhealthy category or had the potential to go bankrupt (distress area). This condition is caused by the low financial ratios owned by the company and the need for follow-up to deal with the problem so that the company avoids the risk of bankruptcy.